Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1743-7075-8-65
|View full text |Cite
|
Sign up to set email alerts
|

The intake of high fat diet with different trans fatty acid levels differentially induces oxidative stress and non alcoholic fatty liver disease (NAFLD) in rats

Abstract: BackgroundTrans-fatty acids (TFA) are known as a risk factor for coronary artery diseases, insulin resistance and obesity accompanied by systemic inflammation, the features of metabolic syndrome. Little is known about the effects on the liver induced by lipids and also few studies are focused on the effect of foods rich in TFAs on hepatic functions and oxidative stress. This study investigates whether high-fat diets with different TFA levels induce oxidative stress and liver dysfunction in rats.MethodsMale Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 55 publications
7
94
0
8
Order By: Relevance
“…Ojieh et al (2009) observed that the rats fed hydrogenated palm oil showed significantly reduced levels of GST, glutathione reductase, GPx activities compared to rats fed unhydrogenated palm oil. Dhibi et al (2011) studied the effect of unmodified and hydrogenated soyabean oil on endogenous antioxidant enzyme activities in rat liver. They observed lower activities for SOD, catalase, GPx in liver homogenate of rats given hydrogenated fat.…”
Section: Discussionmentioning
confidence: 99%
“…Ojieh et al (2009) observed that the rats fed hydrogenated palm oil showed significantly reduced levels of GST, glutathione reductase, GPx activities compared to rats fed unhydrogenated palm oil. Dhibi et al (2011) studied the effect of unmodified and hydrogenated soyabean oil on endogenous antioxidant enzyme activities in rat liver. They observed lower activities for SOD, catalase, GPx in liver homogenate of rats given hydrogenated fat.…”
Section: Discussionmentioning
confidence: 99%
“…In humans with non-alcoholic fatty liver disease circulating FFA are commonly elevated and their plasma levels correlate with disease severity. Also in rats the intake of high-fat diet is related to lipid peroxidation and non-alcoholic fatty liver disease (Dhibi et al 2011). The prominent new mechanisms of liver dysfunctions, especially liver fibrosis, have been pointed out recently, with impact on activation of HSC (Lee and Friedman 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian yang dilakukan oleh Dhibi et al (2011) menyatakan bahwa setelah empat minggu pemberian pakan tinggi lemak trans sebesar 20% dari total energi pakan, menghasilkan pertambahan bobot badan sebesar 25.83 g lebih tinggi dibandingkan dengan tikus yang diberi pakan standar. Peningkatan massa jaringan adiposa akibat diet tinggi minyak trans akan mengakibatkan peningkatan kadar leptin dalam darah.…”
Section: Distance Traveled (Dt) Atau Jarak Tempuhunclassified